Electro-discharge Technology for Drilling Wells and Concrete Destruction - Ushakov, V. Ya.; Vajov, V. F.; Zinoviev, N. T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a concise introduction to the physical foundations of the electro-discharge technology and applies it to the drilling of wells, the demolition of reinforced concrete objects, and the cutting of cracks in rocks and concrete. The electro-physical basis of this technology and the technical implementation of using spark discharge as a "working tool" in the above-mentioned contexts are also briefly considered. The book is intended for all scientists and experts working in the field of resource exploration and extraction, those engaged in building new objects, and in reconstructing or demolishing old ones. It can also be used as a textbook by students and postgraduates, deepening their knowledge of these innovative technologies.
Relevance, physical basis, and problems of large-scale introduction of electro-discharge technology (EDT) -- Impulse electrical strength of rocks and concretes -- Liquids used as insulation and a working medium in EDT -- Discharge channel as a "working tool" in EDT -- Regularities of rock destruction in the process of ED-drilling of wells -- Insulating structure in EDT installations -- Drilling of wells -- Destruction and recycling of reinforced concrete products -- Fragmentation of the filler - the final stage of preparation of reinforced concrete products for utilization -- Breaking and cutting of rocks and concretes.
Keywords: Electric power production; Machinery; Electrical Power Engineering; Machinery and Machine Elements